Measuring the Effectiveness of Community College Faculty Learning Communities on Student Performance (Journal on Excellence in College Teaching, 2024)
One of the challenges facing faculty learning community (FLC) programs in today’s educational climate of assessment and evidence-based research is to demonstrate robust evidence of the impact of FLCs on student success. For this study, the authors defined student success as improvement in performance, persistence, and pathway indicators and used a multi-method approach to assess these outcomes following faculty participation in topic-based FLCs. The three methods included utilizing(1) a survey to assess faculty gains and satisfaction because of their participation in the FLCs, (2) a coding method developed to capture student success as reported by faculty in their final capstone presentations, and (3) a validated survey used in a longitudinal panel design to measure the change in faculties’ beliefs and understandings about classroom equity. The authors discuss the implications of these methods for substantiating that FLCs have an impact on student success and believe that our coding method may be applicable to future FLC studies.